2022
DOI: 10.3389/fpls.2022.1031849
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging with machine learning for non-destructive classification of Astragalus membranaceus var. mongholicus, Astragalus membranaceus, and similar seeds

Abstract: The roots of Astragalus membranaceus var. mongholicus (AMM) and A. membranaceus (AM) are widely used in traditional Chinese medicine. Although AMM has higher yields and accounts for a larger market share, its cultivation is fraught with challenges, including mixed germplasm resources and widespread adulteration of commercial seeds. Current methods for distinguishing Astragalus seeds from similar (SM) seeds are time-consuming, laborious, and destructive. To establish a non-destructive method, AMM, AM, and SM se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Further studies revealed that the average spectral profile of flaxseed has a significant reflectance peak at 420 nm, which is mainly caused by carotenoids ( Yang et al., 2021 ). In addition, the spectral profile shows a clear upward trend in the range of 600-750 nm, which is attributed to the fact that this wavelength corresponds to the vibration of the N-H chemical bond of amino acids in the seeds ( Xu et al., 2022 ). The absorption peak near 980 nm originates from the O-H stretching vibration, which is related to the structure of water molecules ( Yu et al., 2014 ).…”
Section: Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies revealed that the average spectral profile of flaxseed has a significant reflectance peak at 420 nm, which is mainly caused by carotenoids ( Yang et al., 2021 ). In addition, the spectral profile shows a clear upward trend in the range of 600-750 nm, which is attributed to the fact that this wavelength corresponds to the vibration of the N-H chemical bond of amino acids in the seeds ( Xu et al., 2022 ). The absorption peak near 980 nm originates from the O-H stretching vibration, which is related to the structure of water molecules ( Yu et al., 2014 ).…”
Section: Results and Analysesmentioning
confidence: 99%
“…In addition, CARS can more fully consider the correlation between wavelengths, thus better reflecting the characteristics of the data. In hyperspectral data, the CARS algorithm helps select representative characteristic wavelengths more comprehensively, considering that there may be complex relationships between wavelengths ( Xu et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…With applications ranging from crop analysis to real-time plant health and yield monitoring, HSI has proven invaluable in the agriculture field [5,10,23,[28][29][30][31]. Groundbased HSI systems are appropriate for smaller-scale investigations, while airborne setups are suitable for surveying large areas of land.…”
Section: Introductionmentioning
confidence: 99%